2015
DOI: 10.1371/journal.pone.0128155
|View full text |Cite|
|
Sign up to set email alerts
|

Can Newts Cope with the Heat? Disparate Thermoregulatory Strategies of Two Sympatric Species in Water

Abstract: Many ectotherms effectively reduce their exposure to low or high environmental temperatures using behavioral thermoregulation. In terrestrial ectotherms, thermoregulatory strategies range from accurate thermoregulation to thermoconformity according to the costs and limits of thermoregulation, while in aquatic taxa the quantification of behavioral thermoregulation have received limited attention. We examined thermoregulation in two sympatric newt species, Ichthyosaura alpestris and Lissotriton vulgaris, exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…Such methodologies should be used when detecting fine‐scale differences in thermal environments, or when quantifying the energetic costs of thermoregulation. However, the d e index still provides a meaningful, coarse estimator of habitat thermal quality and is thus useful in comparative studies where the habitats being considered differ on a larger scale (Balogová & Gvoždík, ; Sagonas, Kapsalas, Valakos, & Pafilis, ). We found that lizards were more likely to be encountered when thermal quality was high (low d e ; Table ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methodologies should be used when detecting fine‐scale differences in thermal environments, or when quantifying the energetic costs of thermoregulation. However, the d e index still provides a meaningful, coarse estimator of habitat thermal quality and is thus useful in comparative studies where the habitats being considered differ on a larger scale (Balogová & Gvoždík, ; Sagonas, Kapsalas, Valakos, & Pafilis, ). We found that lizards were more likely to be encountered when thermal quality was high (low d e ; Table ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that regardless of habitat type, lizards increased thermoregulatory effort when thermal quality of habitat was poor due to unfavourably hot temperatures (Figure ). Several systems, including tuataras ( Sphenodon punctatus ), black rat snakes ( Elaphe obsoleta obsoleta), painted turtles ( Chrysemys picta ) and two newt species ( Ichthysosaura alpestris and Lissotriton vulgaris ), have been found to increase the accuracy of thermoregulation when experimentally subjected to habitats of poorer thermal quality (Balogová & Gvoždík, ; Besson & Cree, ; Blouin‐Demers & Weatherhead, ; Edwards & Blouin‐Demers, ). However, our study empirically demonstrates that this effect is most pronounced at warmer temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal conditions vary greatly among water bodies (Hadamová and Gvož-dík, 2011; this study), which, together with biotic factors, produce various costs of thermoregulation for amphibian larvae with proven thermoregulatory abilities (Smolinský and Gvoždík, 2012;this study). The vertical thermal stratification in still waters allows replicable and easily measurable thermal conditions for experimental thermoregulatory studies (Gvoždík et al, 2013;Balogová and Gvoždík, 2015). Finally, the less effective thermoregulation in aquatic than in terrestrial taxa allows tests of predictions about the complex thermal strategies in ectotherms (Angilletta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic larval amphibians are an ideal model to analyse thermal adaptations. Despite being capable of regulating their body temperatures (Hutchison & Dupré, ), tadpoles may be limited in their search for favourable microhabitats, for instances when trapped in shallow heated ponds where tadpoles are obligated to act as thermoconformers (Balogová & Gvoždík, ). Thus, their physiological resistances may have been adjusted to the local thermal extremes experienced in their ponds through thermal selection.…”
Section: Introductionmentioning
confidence: 99%